Electronic Nicotine Delivery Systems and Cardiovascular/Cardiometabolic Health. Issue 9 (28th April 2023) - Mears, Matthew J.; Hookfin, Harrison L.; Bandaru, Priya; Vidal, Pablo; Stanford, Kristin I.; Wold, Loren E.
Abstract : The use of electronic nicotine delivery systems, specifically electronic cigarettes (e-cig), has risen dramatically within the last few years; the demographic purchasing these devices is now predominantly adolescents that are not trying to quit the use of traditional combustible cigarettes, but rather are new users. The composition and appearance of these devices has changed since their first entry into the market in the late 2000s, but they remain composed of a battery and aerosol delivery system that is used to deliver breakdown products of propylene glycol/vegetable glycerin, flavorings, and potentially nicotine or other additives. Manufacturers have also adjusted the type of nicotine that is used within the liquid to make the inhalation more palatable for younger users, further affecting the number of youth who use these devices. Although the full spectrum of cardiovascular and cardiometabolic consequences of e-cig use is not fully appreciated, data is beginning to show that e-cigs can cause both short- and long-term issues on cardiac function, vascular integrity and cardiometabolic issues. This review will provide an overview of the cardiovascular, cardiometabolic, and vascular implications of the use of e-cigs, and the potential short- and long-term health effects. A robust understanding of these effects is important in order to inform policy makers on the dangers of e-cigs use.